2017
DOI: 10.1017/s1466252317000044
|View full text |Cite
|
Sign up to set email alerts
|

Global distributions and strain diversity of avian infectious bronchitis virus: a review

Abstract: The poultry industry faces challenge amidst global food security crisis. Infectious bronchitis is one of the most important viral infections that cause huge economic loss to the poultry industry worldwide. The causative agent, infectious bronchitis virus (IBV) is an RNA virus with great ability for mutation and recombination; thus, capable of generating new virus strains that are difficult to control. There are many IBV strains found worldwide, including the Massachusetts, 4/91, D274, and QX-like strains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 154 publications
3
126
0
5
Order By: Relevance
“…In this study, our analyses revealed that the CK/CH/JS/TAHY strain induced severe pathogenicity in 1-day-old SPF chickens with severe kidney and tracheal lesions. Our results confirmed the ability of CK/CH/JS/TAHY strain to induce both respiratory and renal disease which was consistent with QX-like characteristic symptoms (Zou et al, 2010;Bande et al, 2017). As reported, IBV replicated in many respiratory tissues such as trachea, lungs, and air sacs and some urogenital tissues including kidney and even in liver and brain (Cavanagh, 2003;Feng et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, our analyses revealed that the CK/CH/JS/TAHY strain induced severe pathogenicity in 1-day-old SPF chickens with severe kidney and tracheal lesions. Our results confirmed the ability of CK/CH/JS/TAHY strain to induce both respiratory and renal disease which was consistent with QX-like characteristic symptoms (Zou et al, 2010;Bande et al, 2017). As reported, IBV replicated in many respiratory tissues such as trachea, lungs, and air sacs and some urogenital tissues including kidney and even in liver and brain (Cavanagh, 2003;Feng et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…S1 nucleotide sequences of different serotypes differ up to 25% (Cavanagh, 2005). There are 3 hypervariable regions described within the S1 subunit sequence (HVR I aa 38-67, HVR II aa 91-141, HVR III aa 274-387) (Cavanagh et al, 1988), in which most nucleotide substitutions were located (Bande et al, 2017;Lin and Chen, 2017). It was shown that comparison of HVR I and whole S1 gene resulted in the same grouping data (Wang and Huang, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Infectious bronchitis virus (IBV) and Newcastle disease virus (NDV) are 2 of the most important viruses seriously affecting the poultry industry and causing huge economic losses worldwide (Bande et al, 2017;Brown and Bevins, 2017). IBV and NDV belong to the Gammacoronavirus of the Coronaviridae family and the Avulavirus of the Paramyxoviridae family, respectively (http://www.ictv.global).…”
Section: Introductionmentioning
confidence: 99%